ROAD SAFETY CHALLENGES FOR THE 21ST CENTURY. (7th October 2012) - Mohan, D
Abstract : International road traffic fatality data show that low-income and middle-income countries on an average have higher road traffic fatality rates than high-income countries. However, neither the number reported by countries nor WHO estimates have a high correlation with national income. This suggests that higher national incomes do not necessarily produce more road safety. The data indicate that even countries that have similar incomes, vehicle fleet ratios, motor vehicle standards and traffic regulations can have different fatality patterns. This is probably due to other factors influencing fatality rates: urban living patterns, street and highway infrastructure, etc. Recent studies suggest that there are similar variations in fatality rates among cities within countries which cannot be explained by income levels, vehicle technology or basic road design. The paper will focus on the role of the built environment in promoting road safety and challenges ahead in safer road design.